Business as 'YAJNA' initiative of NIT-K alumni for Nation building through entrepreneurship life lessons from industrialist Yajna Narayana Kammaje - Bhat, B. Anantha, Auth. & ed.; Prakash, S. K. Guru, ed.; Karanth, A. S., ed.; Parvatikar, V. B., ed.; Kharod, Hemal, ed. (Mumbai Hemal Mihir Kharod Tik-Talker: Tradepost, 2021)
BUSINESS with a social purpose as spiritual journey , story of growth over time and message ...you too can grow ..
Keywords: Biography -- Businessman; Business Experience